Adolescent Relationship Abuse, Gender Equitable Attitudes, Condom and Contraception Use Self-Efficacy Among Adolescent Girls. Issue 23 (December 2022) - Hill, Ashley V.; Hill, Amber L.; Jackson, Zachary; Gilreath, Tamika D.; Fields, Alana; Miller, Elizabeth
Introduction : Experiencing adolescent relationship abuse (ARA) negatively impacts sexual health and influences risk behaviors of adolescent girls. ARA may be associated with more inequitable gender attitudes among girls, a potentially modifiable factor in violence prevention. This study examines the association among gender equitable attitudes, experiences of ARA, and sexual behaviors among girls participating in Sisterhood 2.0, a community-based violence prevention program implemented in low resource neighborhoods.Methods : Data were from baseline surveys collected for Sisterhood 2.0 implemented in Pittsburgh, PA. Participant demographics, gender equitable attitudes, self-efficacy to use condoms with partners, and self-efficacy to select appropriate contraception were assessed. A latent class analysis (LCA) estimated probability of responses to nine indicators, including sexual behavior self-efficacy and violence. Multigroup LCA by grade (9–12) was also estimated and analyses were performed with SAS V9.4.Results : Female-identified adolescents ages 13–19 ( n = 246) were primarily Black (75%) and evenly distributed across grade in school. Sixty-five percent reported emotional relationship abuse and 31% reported physical abuse within the previous nine months. A three-class solution was best fitting for the LCA. Experiences of violence were related to less equitable gender attitudes, being sexually active, and lower condom and contraception self-efficacy. Younger participants who were sexual minorities with less educated heads of household had more experiences with ARA and less equitable gender attitudes.Discussion : Gender equitable attitudes were lower in adolescent girls with greater experiences of ARA and worse condom and contraception self-efficacy. Integrating discussions about healthy sexual relationships and gender equity may be salient factors in violence prevention.